The Oxygen Environment at Birth Specifies the Population of Alveolar Epithelial Stem Cells in the Adult Lung. (7th March 2016) - Yee, Min; Gelein, Robert; Mariani, Thomas J.; Lawrence, B. Paige; O'Reilly, Michael A.
Abstract: Alveolar epithelial type II cells (AEC2) maintain pulmonary homeostasis by producing surfactant, expressing innate immune molecules, and functioning as adult progenitor cells for themselves and alveolar epithelial type I cells (AEC1). How the proper number of alveolar epithelial cells is determined in the adult lung is not well understood. Here, BrdU labeling, genetic lineage tracing, and targeted expression of the anti-oxidant extracellular superoxide dismutase in AEC2s are used to show how the oxygen environment at birth influences postnatal expansion of AEC2s and AEC1s in mice. Birth into low (12%) or high (≥60%) oxygen stimulated expansion of AEC2s through self-renewal and differentiation of the airway Scgb1a1 + lineage. This non-linear or hormesis response to oxygen was specific for the alveolar epithelium because low oxygen stimulated and high oxygen inhibited angiogenesis as defined by changes in V-cadherin and PECAM (CD31). Although genetic lineage tracing studies confirmed adult AEC2s are stem cells for AEC1s, we found no evidence that postnatal growth of AEC1s were derived from self-renewing Sftpc + or the Scbg1a1 + lineage of AEC2s. Taken together, our results show how a non-linear response to oxygen at birth promotes expansion of AEC2s through two distinct lineages. Since neither lineage contributes to the postnatal expansion of AEC1s, the ability of AEC2s to function as stem cells for AEC1s appears to be restricted to the adult lung. Abstract : The oxygen environment at birth regulates the postnatal expansion of alveolar epithelial cells. AEC2s progressively expand in room air through self-renewal until the lung has reached maximal size. Exposure to low or high oxygen at birth promotes expansion of AEC2s by increasing self-renewal and promoting differentiation of the airway Scgb1a1 + lineage. Contrary to their ability to function as adult stem cells, neonatal AEC2s do not contribute to the postnatal expanding population of AEC1s.